The Markedness of Active and Passive Sentences in Indonesian - Isodarus, Praptomo Baryadi (International Journal of Social Service and Research, 2024)
This research report presents the results of research on the markedness of active and passive voice in Indonesian. The purpose of this study was to determine the markedness of active and passive voice in Indonesian and their implications. The theory used in this study is the concept of markedness proposed by Waugh and Lafford (1994: 2378) and Croft (1990: 64). This research was conducted qualitatively and quantitatively. The results of the study are as follows. The active voice in Indonesian is an unmarked construct, that is, a simple, productive, context-insensitive, more universal sentence, and easier to understand. The passive voice in Indonesian is a marked construct, that is, a more complex, less productive, context-sensitive, more particular sentence, and harder to stand. This markedness has implications for grammar and language learning. For grammar preparation, active voice explanations should be the basis for passive voice explanations so that the rules for forming both types of sentences are easy to understand. For language learning, active voice should be learned first and then passive voice so that both types of sentences are mastered more easily by language learners.